2006
DOI: 10.1086/498222
|View full text |Cite
|
Sign up to set email alerts
|

RYTSI: The Rochester Institute of Technology–Yale Tip‐Tilt Speckle Imager

Abstract: We have constructed a new speckle imaging system that collects a large number of speckle patterns on the detector area of a large-format CCD. The system is called the RIT-Yale Tip-tilt Speckle Imager (RYTSI) because it uses two galvanometric scanning mirrors to tip and tilt each speckle pattern to a different location on the CCD chip. It therefore solves the bandwidth problem of using CCDs in speckle imaging in a unique way: the mirrors direct speckle patterns across the chip with millisecond accuracy, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Horch et al (2009) state that the 562 and 692 nm DSSI filters' central wavelengths are close to those of the V and R of the Johnson U BV RI system. For observations from the RIT-Yale Tip-tilt Speckle Imager (RYTSI) (Meyer et al 2006) reported in Horch et al (2010Horch et al ( , 2012, ∆550 measurements were adopted as ∆V , ∆698 were adopted as ∆R, and ∆754 nm measurements were adopted as ∆I. The ∆814 measurements reported in Reid et al (2001) were assumed to be ∆I.…”
Section: Deblending Photometrymentioning
confidence: 99%
“…Horch et al (2009) state that the 562 and 692 nm DSSI filters' central wavelengths are close to those of the V and R of the Johnson U BV RI system. For observations from the RIT-Yale Tip-tilt Speckle Imager (RYTSI) (Meyer et al 2006) reported in Horch et al (2010Horch et al ( , 2012, ∆550 measurements were adopted as ∆V , ∆698 were adopted as ∆R, and ∆754 nm measurements were adopted as ∆I. The ∆814 measurements reported in Reid et al (2001) were assumed to be ∆I.…”
Section: Deblending Photometrymentioning
confidence: 99%
“…In 2001, we began using a system exclusively designed for CCD-based speckle imaging, RYTSI, designed and built primarily by Reed Meyer, two of us (E.H. and W.vA.), and Zoran Ninkov (Meyer et al 2006). As we gained greater experience with this system, we began to push the limits of the device, including observing some binaries when they were known to be below the diffraction limit.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…A practical example is useful for setting context and objectives for fiber multiplexing. For this exercise we adopt the WIYN 3.5-m telescope as a reference, given its 1 degree diameter FOV, its tradition in speckle imaging with the Rochester Institute of Technology-Yale Tip-Tilt Speckle Imager (RYTSI), DSSI and NESSI systems [5,6,9], as well as its history of multifiber spectroscopy with the Hydra fiber positioner [10]. We explore its potential use for a comprehensive, diffraction-limited imaging follow-up survey of targets for NASA's Transiting Exoplanet Survey Satellite (TESS).…”
Section: Multiplexing Factor Versus Fiber Fovmentioning
confidence: 99%